Study of fungal pathogen in onycomycoses patients attending the teaching hospital - Wankhade, Archana; Ghadage, Dnyaneshwari; Bhore, Arvind (International Journal of Research in Medical Sciences, 2016)
Background: Onychomycosis is commonly caused by dermatophytic group of fungi. Non dermatophytic group of fungi are rarely isolated from nail Onychomycosis due to non dermatophytic molds Cladosporium spp. Aim of the study was to isolate and identify fungal agents from nail clipping of patient clinically having onycomycoses. Methods: Clinical samples from 226 clinically suspected onychomycotic patients were processed in the microbiology laboratory. These nail samples were subjected to 40% KOH examination .Samples were cultured on SDA and SDA chloramphenicol and cycloheximide for isolation of causative agents. These were identified microscopically and macroscopically. Results: Total 35.8% samples were positive for fungus and showed fungal elements in 40% KOH mount amongst which 53.08% showed culture positivity. Conclusions: Dermatophytes are the predominant group of fungi causing onychomycoses. These studies signify the importance of mycological examination in the diagnosis of nail infections for further effective management.